Mutu Organoleptik dan Gizi Biskuit dengan Subtitusi Tepung Jagung (Zea mays) dan Tepung Kacang Merah (Phaseolus vulgaris) - Ety Yuni Ristanti; Muhamad Asrar; Yohanis L Lauika (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2023)
Local food diversification is needed to reduce dependence on imported food. Corn is a source of nutrients and bioactive compounds and red beans are a source of vegetable protein, complex carbohydrates, fiber, B vitamins, folasin, thiamine, calcium, phosphorus and iron. The aim of this study was to analyze the organoleptic quality and nutritional quality of biscuits with substitution of corn flour and red bean flour. This type of research is experimental with a completely randomized design (CRD). The organoleptic quality of color, taste, aroma and texture had a significant effect on biscuit products with corn flour and red bean flour substitutions. Treatment 2 was the most preferred by the panelists. The lower the proportion of corn flour, the lower the value of energy, carbohydrates and fat in the biscuits. The higher the proportion of red bean flour, the higher the protein value of the biscuits. Substitution of corn flour and red bean flour has a significant effect on the organoleptic quality and nutritional quality of biscuits. Further studies are needed to see the content of vitamin, minerals and the self life of biscuits with substitution of corn flour and red bean flour.